Ensure fairness on education management of school among official teachers and unofficial teachers in China - Le, Song; Yasin, Maizura (Human Resources Management Academic Research Society (HRMARS), 2023)
Teaching has become a target career for many people; however, there is a treatment gap between official and unofficial teachers in China. This article aims to examine the specific problem of unfairness between official and unofficial teachers in Chinese schools and analyse the causes of this problem. Four themes were found with respect to the unfairness between unofficial and official teachers: lack of recognition, high work pressure, unavailability of social benefits and inability to attain higher positions. At the same time, the study proposes some positive coping strategies to eliminate or reduce the unfairness between official and unofficial teachers in schools based on the ethics of educational management. Through these strategies, this article hopes to guide educational administrators in their practice to eliminate or reduce the dilemma of unfairness among unofficial teachers.